Electroacupuncture alleviates paclitaxel-induced peripheral neuropathy by reducing CCL2-mediated macrophage infiltration in sensory ganglia and sciatic nerve - Yuanyuan Li; Ruoyao Xu; Muyan Chen; Kaige Zheng; Huimin Nie; Chengyu Yin; Boyu Liu; Yan Tai; Junying Du; Jie Wang; Jianqiao Fang; Boyi Liu (Chinese Medicine)
Abstract Background Paclitaxel-induced peripheral neuropathy (PIPN) is prevalent among patients receiving paclitaxel chemotherapy, which results in sensory abnormality as well as neuropathic pain. Conventional medications lack effectiveness on PIPN. Clinical trials identified beneficial effects of acupuncture on PIPN among patients receiving chemotherapy. Here we explored the mechanisms underlying how acupuncture might alleviate PIPN. Methods A mouse model of PIPN was established by repeated paclitaxel application. Electroacupuncture (EA) was applied at ST36 and BL60 acupoints of model mice. Immunostaining, flow cytometry, behavioral assay, in vivo imaging were utilized for effects determination and mechanism exploration. Results EA ameliorated mechanical and cold pain hypersensitivities, reduced sensory neuron damage and improved loss in intra-epidermal nerve fibers (IENFs) in model mice. Macrophages infiltration were detected in DRG and sciatic nerve of model mice, which was reduced by EA. EA affected M1-like pro-inflammatory macrophage infiltration in DRG, whereas it did not affect M2-like macrophages. DRG neurons released chemoattractant CCL2 that recruited macrophages via CCR2 to DRG. EA reduced CCL2 overproduction by DRG neurons and reduced macrophage infiltration. Blocking CCR2 mimicked EA’s anti-allodynic effect, whereas exogenously applying recombinant CCL2 reversed the ameliorative effect of EA on macrophage infiltration and abolished EA’s anti-allodynia on model mice. EA ameliorated other signs of PIPN, including sensory neuron damage, sciatic nerve morphology impairment and IENFs loss. In mice inoculated with breast cancer cells, EA didn’t affect paclitaxel-induced antitumor effect. Conclusions These findings suggest EA alleviates PIPN by reducing CCL2/CCR2 mediated-pro-inflammatory macrophage infiltration into sensory ganglia as well as the sciatic nerve. Our study supports EA could be used as a potential non-pharmacological therapy for PIPN.